Hubungan Tingkat Stres dengan Emotional Eating saat Pandemi COVID-19 pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Putu Asih Primatanti; Anny Eka Pratiwi; Pande Luh Made Devi Savitri (Aesculapius Medical Journal, 2022)
Due to the Pandemic Situation in 2019, It gave a negative impact on both physical and mental health. Stress causes behavioral and hormonal changes, which improve a person's ability to adapt to environmental changes and survive. This stressful condition may result in a negative response, such as a surge of appetite that tends to be negative, triggering an increase in the consumption of foods high in calories, fat, and sugar. This is linked to the control of emotional eating, which can lead to obesity. As a result, research on the relationship between stress levels and emotional eating during the COVID-19 pandemic is critical. This study's data was collected from 218 students at Warmadewa University's Faculty of Medicine and Health Sciences. This study employs a descriptive-analytic approach, with a cross-sectional design and Spearman test analysis. The goal of this study was to determine the relationship between stress levels and emotional eating in FKIK students at Warmadewa University during the COVID-19 Pandemic. According to the results of the analysis, 144 students (66 percent) reported moderate stress, while 100 reported emotional eating (45.9 percent ) This study's Ï-value of Spearman's test is 0.001, with a correlation value of 0.747, indicating that there is a very strong relationship between stress and emotional eating. As a result, this study supports the existence of a link between stress levels and emotional eating among students at Warmadewa University's Faculty of Medicine and Health Sciences from semester 1 to semester 7 during the COVID-19 pandemic.